2016
DOI: 10.1007/s00787-016-0863-0
|View full text |Cite
|
Sign up to set email alerts
|

Defining cognitive-behavior therapy response and remission in pediatric OCD: a signal detection analysis of the Children’s Yale-Brown Obsessive Compulsive Scale

Abstract: The objective of the study was to examine the optimal Children’s Yale Brown Obsessive-Compulsive Scale (CY-BOCS) percent reduction and raw cutoffs for predicting cognitive-behavioral treatment (CBT) response among children and adolescents with obsessive-compulsive disorder (OCD). Children and adolescents with OCD (N=241) participating in the first step of the Nordic Long-term OCD treatment Study and receiving 14 weekly sessions of CBT in the form of exposure and response prevention. Evaluations were conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 53 publications
0
24
0
Order By: Relevance
“…The CY-BOCS is a clinician-administered interview that assesses OCD symptom severity over the past week. The CY-BOCS total score has demonstrated good reliability, validity, and treatment sensitivity (Scahill, et al, 1997;Skarphedinsson, et al, 2017;Storch, et al, 2010). For this evaluation, conservative benchmarks were used to categorize treatment response (≥35% reduction in total score) and clinical remission (≥55% reduction in total score, or total score cutoff ≤11; Skarphedinsson, et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The CY-BOCS is a clinician-administered interview that assesses OCD symptom severity over the past week. The CY-BOCS total score has demonstrated good reliability, validity, and treatment sensitivity (Scahill, et al, 1997;Skarphedinsson, et al, 2017;Storch, et al, 2010). For this evaluation, conservative benchmarks were used to categorize treatment response (≥35% reduction in total score) and clinical remission (≥55% reduction in total score, or total score cutoff ≤11; Skarphedinsson, et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…The CGI-Severity is clinician-rated scale that provides a global rating of OCD severity, which ranges from "not at all ill" (0) to "extremely ill" (6). Consistent with similar evaluations (Skarphedinsson, et al, 2017;Storch, et al, 2010), scores of "no illness" or "slight illness" were used to designate clinical remission.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Signal detection analysis used to compare judgments of remission at various discrimination thresholds on symptom measures using the YBOCS, showed that a posttreatment YBOCS score of ≤14 was the best predictor of symptom remission defined as having mild or no symptoms on the CGI-S, while a posttreatment YBOCS score of ≤12 was associated with a combination of minimal OCD severity and life satisfaction and adaptive functioning in adults measured by the Quality of Life Enjoyment and Satisfaction Questionnaire (Q-LES-Q) and the Social Adjustment Scale ( Farris et al, 2013 ). A raw YBOCS total score of 11 was also found to be predictive of symptomatic remission in pediatric OCD patients ( Skarphedinsson et al, 2017 ).…”
Section: Recovery: Application Of the Concept To Ocdmentioning
confidence: 99%
“…To track the course of change, it is desirable to assess participants at one or more points during the course of treatment. In the current ECAP, this point is highlighted by Skarphedinsson et al [9], who used the Children's Yale-Brown Obsessive-Compulsive Scale (CY-BOCS) to assess Nordic children before, during, and after cognitive-behavioral therapy for obsessive-compulsive disorders. CY-BOCS scores obtained from independent evaluators were plotted against Clinical Global Impression ratings by clinicians to identify optimal cutoff scores for defining favorable treatment responses and remission of OCD disorders.…”
Section: Research Applicationsmentioning
confidence: 99%